Correlation between Radiological and Pathological Findings in Patients with Mycoplasma pneumoniae Pneumonia - Tanaka, Hiroshi (Frontiers in Microbiology, 2016)
Studies focused on the pathological-radiological correlation of human Mycoplasma (M) pneumoniae pneumonia have rarely been reported. Therefore, we extensively reviewed the literature regarding pathological and radiological studies of Mycoplasma pneumonia, and compared findings between open lung biopsy specimen and computed tomography (CT). Major three correlations were summarized. 1) Peribronchial and perivascular cuffing characterized by mononuclear cells infiltration was correlated with bronchovascular bundles thickening on CT, which was the most common finding of this pneumonia. 2) Cellular bronchitis in the small airways accompanied with exudates or granulation tissue in the lumen revealed as centrilobular nodules on CT. 3) Neutrophils and exudates in the alveolar lumen radiologically demonstrated as air-apace consolidation or ground-glass opacities. In M.pulmonis-infected mice model, pathologic patterns are strikingly different according to host cell-mediated immunity (CMI) levels; treatment with interleukin-2 lead to marked cellular bronchitis in the small airways and treatment with prednisolone or cyclosporin-A lead to neutrophils and exudates in the alveolar lumen. Patients with centrilobular nodules predominant radiologic pattern have a high level of CMI, measuring by tuberculin skin test. From these findings, up-regulation of host CMI could change radiological pattern to centrilobular nodules predominant, on the other hand down-regulation of host CMI would change radiological pattern to ground-glass opacity and consolidation. It was suggested the pathological features of M. pneumoniae pneumonia may be altered by the level of host CMI.